Parents’ Involvement during Science Online Learning of Junior High School Students and Their Learning Outcome - Elizabeth Meiske Maythy Lasut; Jeaclin Grace Maramis (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this quantitative study was to determine the relationship between parents’ involvement during science online learning of Junior High School students and their learning outcome. Researchers constructed a questionnaire about parents’ involvement. The questionnaire was distributed to 56 VII grade students at Adventist Junior High School in Airmadidi. Students’ learning outcome in Science Subject was collected from the subject teacher. This study found out that students often experienced their parents’ involvement by guiding them in online learning, with the Mean Score is 3.64. The level of students’ learning outcome in Science Subject was good, since the Mean Score is 85.75. This study also proved that there is a significant relationship between parents’ involvement during online learning and students’ learning outcome in Science Subject with p = .009. This means that the null hypothesis which stated there was no significant relationship between parents’ involvement during online learning of Junior High School students and their learning outcome is rejected